The separation of signals and background in a nucleon decay experiment - Barr, G; Barr, Giles (1987)
﻿ Two aspects of the problems encountered in searching for nucleon decay in the Soudan 2 detector are discussed. The types of event which are expected are discussed. The most common are Induced by gamma rays from the naturally occurring radioactive isotopes in the cavern rock. A calculation has been developed to predict the rates of such events in the detector and the results agree well when compared with measurements made underground. Some radioactive events cause Compton scattering in the wireplane region of the detector and prohibit the use of a simple multiplicity trigger. Such events have been studied. An electronic trigger system has been designed which will achieve a factor of 103 rejection of these events while remaining efficient for even the most difficult modes of proton decay (75% for p -> K +V ). It is predicted that radioactive triggers will occur at less than 3Hz when the full detector is operating. The neutrino induced background to proton decay has been simulated. The neutrino flux at the detector caused by cosmic ray induced showers in the atmosphere has been predicted. A comprehensive low energy (0.2 GeV to 20 GeV) Monte-Carlo neutrino event generator has been developed as a tool for background studies to proton decay. The Teinteraction of proton decay or neutrino interaction products in the parent nucleus is discussed. It is found that these reinteractions are quite probable, except for K⁺ and K° particles. Data from a low energy neutrino beam experiment has been studied and it is deduced that in some cases, the events seen in the detector will contain visible tracks associated with the disintegration of the parent nucleus. A background estimate for the mode p ➝ K+V from the neutrino interaction Vn ➝ μ~p is presented.